Augmented reality for educative and collaborative environments (2014)
Abstract. This tesis shows the developing and construction process of EducAR (Educative Augmented Reality) an e-learning system for synchronous and asynchronous environments that uses augmented reality as central learning technology. EducAR is composed of a pedagogical model called Augmented Learning, a set of learning strategies and a virtual education application. This application uses a communication and an interaction model. The communication model implements an UDP connection for creating a collaborative learning environment, where all the participants share the 3D augmented reality studied models and can make questions to the teacher about them, the actions made by any user are replicated to all of them, also the answer to the question is replicated to all the participants. The interaction model connects the user activities with the models allowing the rotation in the X and Y axis, zoom, and selection of a specific part of the 3D augmented model, in order to do this two interaction forms are used, mouse and keyboard and the Wiimote.